Hi,

is it cubic root or 3 times the square root?

no it is the number 3

Is it the following?

no that is not correct it is the number three in front of the square root

or the following?

that is correct

ok.

3sqrt(y - 1) - sqrt(8y - 1) = 0

3sqrt(y - 1) = sqrt(8y - 1)

9(y - 1) = (8y - 1)

9y - 9 = 8y - 1

y = 8

Let me know if you have any questions.

ok how about the square root of 3x-6 plus the square root of 2x+6 plus 1 equals zero

I keep getting a no solution on this one

ok. let's solve it.

sqrt(3x - 6) + sqrt(2x + 6) + 1 = 0

There is no solution.

Because square root cannot be negative

I thought so too and my computer program I solve it on tells me there is

the solution is not real number.

thank you once again I greatly appreciate it